Pemberdayaan Ibu-ibu Rumah Tangga melalui Senam Sehat Cantikan (SEHATI) di Dukuh Cantikan Kepatihan Kecamatan Kaliwates Kabupaten Jember - Ismiasih, Novi; Nova Mulyadi, Mochtar (Universitas Sunan Drajat Lamongan, Indonesia, 2024)
Improvements in public health are influenced by changes in advances in science and technology. One aspect that needs to be considered in health is the immune system. As is the case with the people in Dukuh Cantikan, Kepatihan Village, Kaliwates District, Jember Regency, especially mothers, whose daily lives are filled with various activities. All activities carried out every day always take up a lot of time which can cause feelings of boredom and fatigue, thus triggering stress and disrupting health. For this reason, positive activities are needed to overcome this problem. One activity that can maintain the body's immunity is exercise. The aim of this activity is to provide physical and spiritual fitness, as well as provide exercise skills that can broaden mothers' insight. This method of implementing community service uses a form of mentoring and a strategy approach with Asset Based Community Development (ABCD) which is used to improve the quality of human life. This activity was attended by housewives and women from the PKK Dukuh Cantikan, Kepatihan Village, Kaliwates District, Jember Regency. The result of this activity is that apart from producing the next generation as gymnastics instructors, it also increases mothers' awareness of exercising in order to maintain the health of the immune system in the body